(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the general principles of the complex study of neutral emotions in French verbal phraseological units according to their mental characteristics, modal characteristics, intensity characteristics, degree of duration, and control by the central nervous system.